2018
DOI: 10.1371/journal.pone.0207924
|View full text |Cite
|
Sign up to set email alerts
|

Online interest regarding violent attacks, gun control, and gun purchase: A causal analysis

Abstract: BackgroundIncreased interest about gun ownership and gun control are oftentimes driven by informational shocks in a common factor, namely violent attacks, and the perceived need for higher levels of safety. A causal depiction of the societal interest around violent attacks, gun control and gun purchase, both synchronous and over time, should be a stepping stone for designing future strategies regarding the safety concerns of the U.S. population.ObjectiveExamine the causal relationships between unexpected incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Our work builds on a number of recent analyses that employ similar methods, including a comprehensive set of topic models published by Giorgi et al ( 2022 ). In so doing, the current paper contributes to the growing body of work on Black Lives Matter (Crenshaw et al, 2015 ; Gallagher et al, 2018 ; Lebron, 2017 ), the broader literature on online social movements (Hara and Huang, 2011 ; Harlow, 2012 ; Tufekci, 2017 ), and the still nascent study of attentional dynamics in virtual environments (Freelon et al, 2020 ; Gunn et al, 2018 ; Hendricks and Vestergaard, 2019 ).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our work builds on a number of recent analyses that employ similar methods, including a comprehensive set of topic models published by Giorgi et al ( 2022 ). In so doing, the current paper contributes to the growing body of work on Black Lives Matter (Crenshaw et al, 2015 ; Gallagher et al, 2018 ; Lebron, 2017 ), the broader literature on online social movements (Hara and Huang, 2011 ; Harlow, 2012 ; Tufekci, 2017 ), and the still nascent study of attentional dynamics in virtual environments (Freelon et al, 2020 ; Gunn et al, 2018 ; Hendricks and Vestergaard, 2019 ).…”
Section: Introductionmentioning
confidence: 85%
“…An autoregression (AR) predicts the value of a variable on a day as a function of time-lagged values of both that variable and other variables. Autoregression was used successfully by Gunn et al ( 2018 ) to examine online timecourse data about shootings and gun control as a proxy for political engagement. We looked at two autoregressions: Model I: “ Naive ” AR The first autoregression model considered only the number of tweets per day for a group, and predicted these as a function of their own lagged tweets plus lagged protests per day as an exogenous variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies analyzing gun-related Internet searches have found that U.S. search volume for the term "buy gun" is correlated to the number of firearm background checks performed in the U.S. between 2008 and 2015 (Pearson's r = 0.84) 12 . Studies have also found that search volume for firearm-related terms changes in response to mass shootings 5,[12][13][14][15][16][17][18] . These studies measured overall increases in the volume of search terms before and after mass shootings and found increases of tens or even hundreds of percent.…”
Section: Introductionmentioning
confidence: 99%
“…The substantial attention given to the coverage of public mass shootings in the media is rooted, at least in part, in the interplay between the interest among the general public to seek and consume information, and the motivation of media outlets to provide information about such events. The interest of the general public in mass shooting events can be attributed to a range of motivations, from general curiosity or a desire to obtain information about current news to a concern for public and personal safety (Gunn, Ter Horst, Markossian, & Molina, ; Menachemi, Rahurkar, & Rahurkar, ). Levin and Wiest () recently explored public interest in information after mass shootings (specifically school shootings) identified information seeking, specifically in the context of public and personal protestation and safety, as a generally strong motivator for consuming news about such an event.…”
mentioning
confidence: 99%